The rising concept of leadership in Public Sector units – A conceptual analysis (International Journal of Scientific Research and Management (IJSRM), 2017)
Concept of leadership exists in every sphere of our living starting from the leader of a family to the leader of an organization. A leader in an organization is interpreted as someone who sets the direction in an effort & influences people to follow them. Under human resources management leadership is a very dynamic concept which involves directing the activities of a group towards a shared goal. Organizational leadership is dual focused management approach which focuses on which is best for the individuals & what is best for the group as a whole simultaneously. It provides a sense of cohesiveness, personal development and higher level of satisfaction among those who are conducting the work. And it provides a proper sense of direction and vision, an alignment with the environment, a healthy mechanism for innovation and creativity. There are many important studies on leadership in the public administration discipline, as public sector is also playing a very crucial role in today’s economy. There is a difficulty when considering leadership of public professionals that is most theories are not developed within this context but are usually developed for the business settings and are applied to public segment. This article helps to fill that gap by analyzing the role of public sector leaders, who play an important role for their employees. It has a positive influence on employee job outcomes. This paper will show that leadership strongly influences work meaningfulness which relates to job outcomes. The impact and extent of leadership and work meaningfulness are higher in public sector. The present study will help us to know about the importance of leadership in public sector and its impact on employees